2022
DOI: 10.1002/aenm.202201493
|View full text |Cite
|
Sign up to set email alerts
|

Carbon/Lithium Composite Anode for Advanced Lithium Metal Batteries: Design, Progress, In Situ Characterization, and Perspectives

Abstract: The lithium metal anode is a competitive candidate for next‐generation lithium‐ion batteries for its low redox potential and ultra‐high theoretical specific capacity. Nevertheless, obstacles regarding heterogeneous lithium deposition, dendrite growth, and poor Coulombic efficiency limit its practical application. Among rational electrode designs, carbon materials have been regarded as feasible hosts for stabilizing lithium to address the above issues due to their light weight, high conductivity, and adjustable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 221 publications
0
23
0
Order By: Relevance
“…A recent trend in recent papers has been to modify current collectors to improve lithium nucleation and growth behavior. ,, Previously we have shown that the use of ZnO-coated Ni foam leads to the formation of a lower surface area lithium and overall leads to better electrochemical performance . Yet, achieving maximum electrochemical performance requires the optimization of the ZnO layer thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent trend in recent papers has been to modify current collectors to improve lithium nucleation and growth behavior. ,, Previously we have shown that the use of ZnO-coated Ni foam leads to the formation of a lower surface area lithium and overall leads to better electrochemical performance . Yet, achieving maximum electrochemical performance requires the optimization of the ZnO layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, two alternative electrochemical methods, defined as “conventional” and “reservoir” ( vide infra ), have been used to investigate the evolution of the CE in ZnO-coated Ni foam current collectors for AFBs. The effect of the modification of the current collector and electrolyte solution on the electrochemical plating and stripping of metallic lithium has already been studied in half-cell setups. , Using three-dimensional (3D) structures coated with lithiophilic materials is an approach that has recently received considerable attention. , As studied previously, a thin layer of ZnO on a 3D current collector influences the morphology of deposited lithium and improves electrochemical performance. Here, 3D Ni foam coated by ZnO was used to characterize the CE of LMBs and AFBs.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable lithium-ion batteries (LIBs) have been previously considered as promising candidates for application in intermittent energy storage, due to their decent reversibility, high security, and superb energy efficiency. [6][7][8] However, LIBs, mostly based on the ion intercalation mechanism are now approaching their theoretical energy density of 300-350 W h kg À1 and can satisfy neither the large-scale energy storage scenario, [9][10][11] such as the power grids aforementioned, nor the prevailing electric vehicles. Hence, it is urgent to develop a powerful and reliable energy storage system on the way of exploiting and utilizing the natural energy resources with almost no carbon emission (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on increasing the energy density of rechargeable lithium-ion batteries (LIBs), lithium metal with a high theoretical specific capacity (3860 mAh g −1 ) and low redox potential (−3.040 V vs. standard hydrogen electrode) have been extensively investigated [1][2][3][4]. However, uncontrollable lithium dendrite growth and dead lithium (inactive lithium) generation during repeated cycles lead to instability at the lithium metal anode interface, which results in a waste of lithium resources, a low Coulombic efficiency (CE), and even incurs safety hazards, which seriously restrict their practical applications [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%